Prevalence and factors associated with unmet needs in post‐treatment cancer survivors: A systematic review - Miroševič, Špela; Prins, Judith B.; Selič, Polona; Zaletel Kragelj, Liljana; Klemenc Ketiš, Zalika (European journal of cancer care, 2019)
Cancer survivors may experience unmet needs beyond the end of their treatment. This paper aimed to explore the prevalence and most frequently found unmet needs and to identify factors associated with higher levels of total unmet needs and with each domain separately. Five databases were searched using the keywords neoplasms, survivors, needs assessment, health services’ needs and demands. The results were presented based on the strength of the evidence (strong, moderate and weak association) and the categorisation of the pooled prevalence of at least one unmet need (high, moderate, low). Twenty‐six studies were included in the review. A higher prevalence of at least one reported unmet need was observed in survivors with less time since treatment and in women with breast cancer. The most frequently reported unmet needs were fear of cancer recurrence and requesting up to date information. Strong evidence was found for an association between a higher number of unmet needs and younger age, higher anxiety and poorer quality of life. Future studies on unmet needs should report how unmet needs are associated with each domain separately. This might solve the inconclusive evidence found for the stage of the disease at diagnosis and depression.